Modulation of Toll-Like Receptor Activity by Leukocyte Ig-Like Receptors and Their Effects during Bacterial Infection. (20th June 2010) - Pilsbury, Louise E.; Allen, Rachel L.; Vordermeier, Martin
Abstract : Toll-like receptors (TLRs) are a potent trigger for inflammatory immune responses. Without tight regulation their activation could lead to pathology, so it is imperative to extend our understanding of the regulatory mechanisms that govern TLR expression and function. One family of immunoregulatory proteins which can provide a balancing effect on TLR activity are the Leukocyte Ig-like receptors (LILRs), which act as innate immune receptors for self-proteins. Here we describe the LILR family, their inhibitory effect on TLR activity in cells of the monocytic lineage, their signalling pathway, and their antimicrobial effects during bacterial infection. Agents have already been identified which enhances or inhibits LILR activity raising the future possibility that modulation of LILR function could be used as a means to modulate TLR activity.